TEACHER’S MANAGEMENT IN ARABIC INSTRUCTION - Roviin Roviin (Ta'dib, 2017)
In Arabic instruction, teacher’s management is the  central point for the empowerment of other learning resources, so that educational objectives will be achieved. This article is the result of reflection, in which the competence of Arabic teachers is an important requirement in planning, implementation, and evaluating activities, which has been regulated by the Regulation of the Minister of ducation and Culture as well as the Decree the Minister of Religious Affairs. The planning begins with the division of Arabic teachers’  job description, the setting up of learners, and the preparation of lesson plans. The implementation consists of pre-activities, whilst activirties, and post-activities which end with an assessment.